Comparative study of some applications made in the Vue.js and React.js frameworks - Novac, Cornelia Mihaela; Novac, Ovidiu Constantin; Sferle, Raluca Marina; Gordan, Mircea Ioan; Bujdoso, Gyongyi; Dindelegan, Camelia Maria (2021 16th International Conference on Engineering of Modern Electric Systems (EMES), 2021)
It is known that the demand for faster and better applications and tools has increased nowadays. JavaScript frameworks come with a helpful hand in terms of popularity, easy-to-use, and integration, using new technology to favour developer and user. It is probably the manager's choice which framework is the best for his project. Nevertheless, two main JavaScript frameworks will be compared in this analysis: Vue.js and React.js.